Chasing Performance of Protected Area Management in Nepal - Tiwari, Achyut (Journal of Tourism and Himalayan Adventures, 2022)
Nepal represents a unique biodiversity which is associated with higher topographic variation and regional climate. The landscape 60 m above sea level reaching its maximum elevation up to 8.8 kilometers, strong monsoon system entering from south east of Nepal and westerly entering from the west contribute to considerable variety of life forms in the relatively smaller land area. The rich biodiversity not only forms the part of many ecological systems in the region but also provides varieties of ecosystem service in the region. Realizing the efficacy of conservation of biological and natural resources, the early conservation efforts were initiated in Nepal in the early 1970s when the concept of Protected Area (PAs) was in its rudimentary stage. Since then PA management achieved its greater heights in Nepal marching to include 30% land area of Nepal under PAs, which is perfectly following AICHI Target of 2030. In this communication, we have accessed the achievements and lapses in PAs management in Nepal. It is claimed the considerable increase in land areas and types of protected areas, and visible lapses in PAs management. Basically, it is very critical to pinpoint biodiversity hotspots and species endemism before setting aside protected areas for conservation. It emphasizes that it has been a high time to initiate the conservation of several small protected areas in order to complement the existing single large protected area system. Further, I recommend the equal conservation consciousness for areas outside conservation areas in Nepal with more focus on educating people for caring Mother Nature.